Optimization of Literacy Clinic Empowerment: An Efforts to Improve Teachers' Ability in Dealing with High Grade Students Who Have Difficulties in Reading - Nurjamin, Asep; Nurwahidah, Lina Siti; Nugraha, Fajar (Universitas Negeri Semarang, 2024)
One of the learning problems experienced by high school teachers is the difficulty of teaching students who have difficulty reading. This problem often makes teachers helpless. Therefore, a training program entitled